2018
DOI: 10.22271/tpr.2018.v5.i2.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various plant growth regulators on in vitro seed germination and shoot organogenesis in Tectona grandis L.f.

Abstract: In the present study efforts were made to enhance in vitro seed germination and achieve shoot organogenesis through different explants of Tectona grandis, a hardwood timber species known throughout the world for its high-value wood. Seed germination was significantly affected by seed inoculation on different strengths of MS medium and different GA 3 concentrations. Different strengths of MS media combined with different GA 3 concentration significantly affect seed germination in vitro. Maximum seed germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Root tips from in vitro raised seedlings of Citrus indica cultured on full strength and half strength MS supplemented with 2,4-D, IBA, NAA, Kn and BAP in varying concentrations (0.25 -1.5 mg/l) and combinations did not show shoot initiation even after one month of observation. Similarly, Mishra et al (2018) tested various explants viz., leaf, internode, hypocotyls and root of seedlings of Tectona grandis for shoot organogenesis and observed that the root explants were least responsive.…”
Section: Resultsmentioning
confidence: 99%
“…Root tips from in vitro raised seedlings of Citrus indica cultured on full strength and half strength MS supplemented with 2,4-D, IBA, NAA, Kn and BAP in varying concentrations (0.25 -1.5 mg/l) and combinations did not show shoot initiation even after one month of observation. Similarly, Mishra et al (2018) tested various explants viz., leaf, internode, hypocotyls and root of seedlings of Tectona grandis for shoot organogenesis and observed that the root explants were least responsive.…”
Section: Resultsmentioning
confidence: 99%
“…Mercuric chloride atau merkuri biasanya digunakan untuk mendapatkan eksplan steril dari benih dan tunas jati (Kozgar & Shahzad, 2012;Antony et al, 2015;Fauzan, Supriyanto, & Tajuddin, 2017;Mishra, Bhadrawale, & Yadav, 2018). Merkuri jika dibuang langsung ke tanah akan mencemari lingkungan, maka diperlukan bahan sterilan yang lebih ramah lingkungan.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian menggunakan larutan merkuri 0,1%-1% dengan waktu perendaman antara 3 -5 menit untuk sterilisasi permukaan (Kozgar & Shahzad, 2012;Mishra et al, 2018 ( Ivanova & Van Staden, 2008;Rahman, Haider, Hossain, & Islam, 2011;Sianturi et al, 2017). Pada media modifikasi konsentrasi KNO3 (kalium nitrat) lebih banyak dibandingkan dengan NH4NO3 (ammonium nitrat).…”
Section: Analisis Dataunclassified
“…Another tissue culture utilization opportunity is to be able to cross distantly related species to regenerate hybrid novels through protoplast fusion, production of double monoploid crops with kolkisin treatment from haploid cultures to reach homozygous strains faster in breeding programs, seed production of certain plants that require a high level of genetic conservation for seed production, as a better scope and future for the production of important phytopharmaceuticals, as well as helping the successful production of valuable, specific plant chemicals that have not yet been discovered. Successful propagation of tissue cultures of woody plants has been widely reported, among others, in the species Tectona grandis [34], Santalum album [29], Acacia sinuate [18] and Aquilaria malaccensis Lam [30]. Separate screenings related to the influence of seasons [3,5,6,8,21] basic media [16,35] and growth-stimulating substances [13,14,34] have been widely reported as well as the results of comprehensive screening related to the three factors mentioned above [1,2,4,9,12,13,18,20,22,23,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Successful propagation of tissue cultures of woody plants has been widely reported, among others, in the species Tectona grandis [34], Santalum album [29], Acacia sinuate [18] and Aquilaria malaccensis Lam [30]. Separate screenings related to the influence of seasons [3,5,6,8,21] basic media [16,35] and growth-stimulating substances [13,14,34] have been widely reported as well as the results of comprehensive screening related to the three factors mentioned above [1,2,4,9,12,13,18,20,22,23,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%